Acute Hemorrhagic Conjunctivitis by Enterovirus 71 - Brahm Prakash Guliani; Pratyush Ranjan; Anurag Narula; Shashi Khare (Delhi Journal of Ophthalmology)
Enterovirus 71 (EV71) infection is generally asymptomatic but it may cause hand foot mouth disease (HFMD), severe pulmonary edema, meningoencephalitis, acute flaccid paralysis and even death during epidemic outbreaks. We are presenting a case of an acute hemorrhagic conjunctivitis (AHC) in a fourteen year old female who presented to us with sudden onset of pain, redness, lid swelling &subconjunctival hemorrhage with watery discharge involving both the eyes for four days in which EV71 virus was isolated from conjunctival swab. To the best of our knowledge this is the first case of AHC reported to be due to EV71.